Do all new brooms sweep clean? Evidence for outside bank appointments - Kick, Thomas; Nehring, Inge; Schertler, Andrea (Journal of Banking & Finance, 2017)
Banks in bad financial shape are more likely to appoint executive directors from the outside than those in good shape. It is, however, not clear whether all of these appointments necessarily lead to the desired turnaround. We analyze the performance effects of new board members with external boardroom experience (outsiders) by distinguishing between good and bad managerial abilities of executives based on either ROA or risk-return efficiency of their previous employers. Our results show that banks appointing bad outsiders underperform other banks while those appointing good outsiders do so to a lesser extent. The performance differentials are highly pronounced in high-risk banks and in the post-crisis period.